2021
DOI: 10.1038/s41467-020-20293-y
|View full text |Cite
|
Sign up to set email alerts
|

Controlling hot electron flux and catalytic selectivity with nanoscale metal-oxide interfaces

Abstract: Interaction between metal and oxides is an important molecular-level factor that influences the selectivity of a desirable reaction. Therefore, designing a heterogeneous catalyst where metal-oxide interfaces are well-formed is important for understanding selectivity and surface electronic excitation at the interface. Here, we utilized a nanoscale catalytic Schottky diode from Pt nanowire arrays on TiO2 that forms a nanoscale Pt-TiO2 interface to determine the influence of the metal-oxide interface on catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…With an integrated batch reactor, the evolved chemicurrent and catalytic conversion rate of reactant molecules are monitored simultaneously under the reaction environment. Therefore, the generation of hot electrons is definitely observed in the manner of dramatically increasing chemicurrent, when a full oxidation of methanol (MeOH) occurs at above 40 °C, as shown in Figure e . It is evident that the chemicurrent yield in MeOH oxidation is influenced by dynamics of the hot electron relaxation at the metal-oxide interface.…”
Section: Representative Operando Analysis Techniquesmentioning
confidence: 90%
See 2 more Smart Citations
“…With an integrated batch reactor, the evolved chemicurrent and catalytic conversion rate of reactant molecules are monitored simultaneously under the reaction environment. Therefore, the generation of hot electrons is definitely observed in the manner of dramatically increasing chemicurrent, when a full oxidation of methanol (MeOH) occurs at above 40 °C, as shown in Figure e . It is evident that the chemicurrent yield in MeOH oxidation is influenced by dynamics of the hot electron relaxation at the metal-oxide interface.…”
Section: Representative Operando Analysis Techniquesmentioning
confidence: 90%
“…(e) Schematic illustration of Pt nanowires/TiO 2 nanodiode and measured current density plots at the elevated reaction temperature under the methanol oxidation reaction. Reproduced under the terms of the CC-BY Creative Commons Attribution 4.0 International license () from ref . Copyright 2021, The Authors, published by Springer Nature.…”
Section: Representative Operando Analysis Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the high surface to volume ratio, adjustable size and structure, rich surface chemistry, and adjustable visible light absorption, the nanoscale metal oxide clusters have emerged as promising cophotocatalysts in the photocatalytic field, which has greatly boosted the advancement of many photocatalytic applications, such as water splitting, nitrogen fixation, organic pollutants degradation, and organic synthesis. Compared to the corresponding nanoparticles, the cluster structure has fascinating photocatalytic activity due to the inherent structure and enhanced quantum size effect. Herein, we prepared tin oxide (SnO 2 ) clusters modified g-C 3 N 4 (SnO 2 @g-C 3 N 4 ) for a high-efficient photocatalytic hydrogen peroxide generation reaction. The SnO 2 @g-C 3 N 4 is obtained by introducing acetic acid tin (C 8 H 12 O 8 Sn) in the calcination process of urea.…”
Section: Introductionmentioning
confidence: 99%
“…Using the DFT method, from the standpoint of the energy approach, it was explained why the sensory response of MPcF 4 films to ammonia is noticeably higher than that of MPc films. The use of various approximations of the DFT method has shown that they can successfully solve similar problems and answer questions from sensor developers [32][33][34]. In particular, a numerical experiment using DFT methods makes it possible to determine the activation barrier, the change in free energy and the position of the Fermi level when gas molecules land on the sensor surface, and to predict the effect of moisture and other types of surface modification.…”
Section: Introductionmentioning
confidence: 99%